2011
DOI: 10.1039/c1pp05087g
|View full text |Cite
|
Sign up to set email alerts
|

Role of entropy in supramolecular photochirogenesis: enantiodifferentiating photoisomerization of cyclooctenes in chiral sensitizer-immobilized MCM-41 cavities

Abstract: To examine the effects of confinement, or low-entropy environments, we employed the mesoporous silicate MCM-41 modified with optically active benzenetetracarboxylates as chiral reaction media to effect the enantiodifferentiating photoisomerization of (Z)-cyclooctene and (Z,Z)-1,5-cyclooctadiene. The ee of the (E)-isomer produced and its temperature dependence behavior in MCM-41 were completely different from those observed in homogeneous solutions. Immobilizing the sensitizer in MCM-41 reduced the contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(4 reference statements)
2
1
0
Order By: Relevance
“…This unusual reduced entropy is rare but not unprecedented. Inoue et al demonstrated that for photoisomerization of ( Z )-cyclooctene in a mesoporous material such as MCM-41, ΔΔ S ‡ S‑R was significantly reduced from −4.5 to 0.6 cal mol –1 K –1 in methylcyclohexane, due to restricted movement of the substrate in the pores . Likewise, the reduced entropy observed in this study can be attributed to limited molecular movement resulting from frozen-state-solvent solids at low temperatures.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This unusual reduced entropy is rare but not unprecedented. Inoue et al demonstrated that for photoisomerization of ( Z )-cyclooctene in a mesoporous material such as MCM-41, ΔΔ S ‡ S‑R was significantly reduced from −4.5 to 0.6 cal mol –1 K –1 in methylcyclohexane, due to restricted movement of the substrate in the pores . Likewise, the reduced entropy observed in this study can be attributed to limited molecular movement resulting from frozen-state-solvent solids at low temperatures.…”
supporting
confidence: 55%
“…Inoue et al demonstrated that for photoisomerization of (Z)-cyclooctene in a mesoporous material such as MCM-41, ΔΔS ‡ S-R was significantly reduced from −4.5 to 0.6 cal mol −1 K −1 in methylcyclohexane, due to restricted movement of the substrate in the pores. 30 Likewise, the reduced entropy observed in this study can be attributed to limited molecular movement resulting from frozen-statesolvent solids at low temperatures. This is further supported by Raman spectra of the DMSO−acetone mixture used for the present reaction (see Figure S4 and the relevant discussion).…”
supporting
confidence: 51%
“…The coherence duration time that is appropriate to quantum logic function in DNA is provided by qualities of the DNA itself, and the crystalline nature of DNA provides a coherent stability that was intuited by Schrödinger. As occurs in DNA, the regular and precise design of the nanospace of a crystal limits the degrees of freedom upon which entropic factors such as temperature or solvation can have any effect [ 13 ], because if there is only one degree of freedom in a situation then there is zero entropy that can be induced in that situation. Thus the quantum logic in DNA by its nature involves a process of topological change in the DNA molecule, and topological quantum logic by its nature is a fault-tolerant process.…”
Section: Coherence Stabilitymentioning
confidence: 99%